Systematic Literature Review of Digital-Based Public Service Innovation in Civil Servant Pension Administration Services - Agustino Yamlean; Dian Ferriswara; Fedianty Augustinah; Sri Kamariyah (International Forum of Researchers and Lecturers, 2026)
Digital transformation in the public sector has driven various service innovations, including pension administration services for State Civil Apparatus (ASN). This study aims to analyze the development of digital-based public service innovations in pension administration and identify the benefits and challenges of their implementation. This study used the Systematic Literature Review (SLR) method by reviewing various relevant scientific articles from national journals that discuss the digitalization of public services and pension administration. The literature selection process was carried out systematically to identify, evaluate, and synthesize research findings related to digital-based pension service innovations. The review results indicate that digitalization of pension administration services through the use of electronic service applications and platforms can improve administrative efficiency, accelerate data verification and pension fund disbursement, and increase transparency and accountability in public services. The implementation of digital services also contributes to simplifying bureaucratic procedures and increasing service accessibility for retirees. However, the literature review also revealed challenges in implementing digital pension services, including low digital literacy among retirees, limited access to technological devices, and suboptimal dissemination of service information. The findings of this study indicate that the success of digital-based service innovations depends not only on technology, but also on human resource readiness, the organizational capacity of government institutions, and the level of public acceptance of the use of digital technology. Therefore, developing digital-based pension services requires a comprehensive strategy.